2003
DOI: 10.1095/biolreprod.102.014977
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Trophoblast Invasion: Implications for the Pathogenesis of Intrauterine Growth Retardation and Preeclampsia

Abstract: Maternal uteroplacental blood flow increases during pregnancy. Altered uteroplacental blood flow is a core predictor of abnormal pregnancy. Normally, the uteroplacental arteries are invaded by endovascular trophoblast and remodeled into dilated, inelastic tubes without maternal vasomotor control. Disturbed remodeling is associated with maintenance of high uteroplacental vascular resistance and intrauterine growth restriction (IUGR) and preeclampsia. Herein, we review routes, mechanisms, and control of endovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
706
2
47

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,066 publications
(770 citation statements)
references
References 44 publications
15
706
2
47
Order By: Relevance
“…The more severe forms of early-onset PE and idiopathic FGR are thought to originate as a consequence of impaired trophoblast function, with limited EVT invasion into maternal decidua and underlying myometrium in the early stages of pregnancy. 78 Defective trophoblast differentiation and shallow invasion of trophoblasts are key lesions commonly observed in PE placentae. 79 Placentae from FGR pregnancies show reduced trophoblast cell proliferation, reduced villous vascularisation and elevated vascular impedance.…”
Section: Emt Is Implicated In Pathological Pregnanciesmentioning
confidence: 99%
“…The more severe forms of early-onset PE and idiopathic FGR are thought to originate as a consequence of impaired trophoblast function, with limited EVT invasion into maternal decidua and underlying myometrium in the early stages of pregnancy. 78 Defective trophoblast differentiation and shallow invasion of trophoblasts are key lesions commonly observed in PE placentae. 79 Placentae from FGR pregnancies show reduced trophoblast cell proliferation, reduced villous vascularisation and elevated vascular impedance.…”
Section: Emt Is Implicated In Pathological Pregnanciesmentioning
confidence: 99%
“…It was suggested that the gestational age dependent reduction in HIFs likely reflects their degradation in response to increasing oxygen concentration [42,43]. In support of this premise is the finding of increased placental expression of HIF-1α and HIF-2α in pregnancies complicated by PE [44], which are also characterized by placental hypoxia [1,3,45].…”
Section: Discussionmentioning
confidence: 96%
“…Successful placentation and maintenance of pregnancy requires that invasive and hemostatic processes in trophoblasts are tightly regulated [1][2][3][4]. The plasmin/plasminogen activator system plays a key role in modulating these pathways at the maternal-fetal interface [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Among the specialized differentiated trophoblast cells of the placentation site are populations of cells with the capacity to migrate, invade the uterine parenchyma and associate with the vasculature. 3,[6][7][8] These cell types are defined by their relationships with the uterine spiral arteries. Those cells located between blood vessels are referred to as interstitial invasive trophoblast cells, and those cells embedded within vessels and contributing to the replacement of the endothelium are termed endovascular invasive trophoblast cells.…”
mentioning
confidence: 99%